1991
DOI: 10.1007/bf00587816
|View full text |Cite
|
Sign up to set email alerts
|

X-linked deafness, stapes gushers and a distinctive defect of the inner ear

Abstract: The association of X-linked mixed deafness with stapes gusher has been recognized for 20 years, and imaging studies by polytomography have shown dilatation of the lateral end of the internal auditory meatus (IAM) in some cases. We have made genetic linkage studies in 7 pedigrees in whom deafness was inherited in an X-linked manner. All patients had a full range of audiometric and vestibular function tests. Thin section high resolution CT in two planes was used to assess the state of the middle and inner ears. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
111
1
7

Year Published

1998
1998
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 199 publications
(123 citation statements)
references
References 12 publications
4
111
1
7
Order By: Relevance
“…Other studies have suggested deficiency of bone between the internal auditory canal and the vestibule (39) and enlargement of the vestibular aqueduct (42). At middle ear surgery, the stapes has been reported to be congenitally fixed in some patients but not in others (5,(38)(39)(40)(41). In patients with a mobile stapes, we believe that the CHL is caused by an abnormal communication between the internal auditory canal and the inner ear (either the scala vestibuli of the cochlea or the vestibule), resulting in a pathologic third window that worsens air-conducted thresholds and improves bone-conducted thresholds.…”
Section: Dfn-3 (X-linked Deafness With Stapes Gusher)mentioning
confidence: 91%
See 1 more Smart Citation
“…Other studies have suggested deficiency of bone between the internal auditory canal and the vestibule (39) and enlargement of the vestibular aqueduct (42). At middle ear surgery, the stapes has been reported to be congenitally fixed in some patients but not in others (5,(38)(39)(40)(41). In patients with a mobile stapes, we believe that the CHL is caused by an abnormal communication between the internal auditory canal and the inner ear (either the scala vestibuli of the cochlea or the vestibule), resulting in a pathologic third window that worsens air-conducted thresholds and improves bone-conducted thresholds.…”
Section: Dfn-3 (X-linked Deafness With Stapes Gusher)mentioning
confidence: 91%
“…The air-bone gap is greater in the lower frequencies, and the stapedial reflex may be preserved (5,41). Radiologic studies typically demonstrate dilation of the internal auditory canal, often with deficiency of bone between the internal auditory canal and cochlea (40)(41)(42)(43). Other studies have suggested deficiency of bone between the internal auditory canal and the vestibule (39) and enlargement of the vestibular aqueduct (42).…”
Section: Dfn-3 (X-linked Deafness With Stapes Gusher)mentioning
confidence: 99%
“…Afflicted individuals are characterized clinically by mixed conductive and sensorineural hearing loss and pathologically by defects in the bony labyrinth of the inner ear. These abnormalities include Mondini dysplasia, cochlear hypoplasia, and stapes fixation (Arellano et al 2000;Phelps et al 1991). Mondini dysplasia is a common radiological finding in cases of idiopathic congenital hearing loss (Zheng et al 2002), and elucidating its molecular basis will aid in our understanding of the causes of deafness with unknown etiologies.…”
Section: Introductionmentioning
confidence: 99%
“…The syndrome of X-linked progressive mixed deafness (with perilymphatic gusher during stapes surgery) was first described in 1974. The bulbous enlargement of the internal auditory canal, typically located in the lateral portion of the IAC fundus, was depicted already in the 1970 s in conventional coronal polytomographic examinations [19]. Another typical finding is an osseous defect in the bony partition between the IAC and the perilymph space of the inner ear near the basal turn of the cochlea [20].…”
mentioning
confidence: 99%
“…Normally, in healthy subjects, the lateral end of the IAC is comprised of a subtle bony plate (lamina cribrosa). This membranous bony structure is penetrated by the vestibular nerves, the facial nerve and the small branches of the cochlear nerve running from the spiral ganglion to the cochlear end organs [19]. The bony plate and the spiral ganglion separate the subarachnoid space in the IAC from the perilymph space.…”
mentioning
confidence: 99%